2019
DOI: 10.3324/haematol.2018.213009
|View full text |Cite
|
Sign up to set email alerts
|

The lifespan quantitative trait locus gene Securin controls hematopoietic progenitor cell function

Abstract: The percentage of murine hematopoietic stem and progenitor cells, which present with a loss of function upon treatment with the genotoxic agent hydroxyurea, is inversely correlated to the mean lifespan of inbred mice, including the long-lived C57BL/6 and short-lived DBA/2 strains. Quantitative trait locus mapping in BXD recombinant inbred strains identified a region spanning 12.5 cM on the proximal part of chromosome 11 linked to both the percentage of dysfunctional hematopoietic stem and progenitor cells as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…We have previously demonstrated, that epigenetic age-predictions with our 3 CpG pyrosequencing agepredictor are accelerated in DBA/2 mice, as compared to C57BL/6 mice, which may reflect the different life expectancy of these mouse strains (Han et al, 2018). Furthermore, we demonstrated that age-predictions with this predictor were also accelerated in C57BL/6 mice with quantitative trait locus insertion from DBA/2 into the congenic C57BL/6 chromosome 11, which was expected to be associated with the shorter lifespan of DBA/2 (referred to as Line A mice) (Brown et al, 2019). We now determined, within the same samples, whether the epigenetic age-acceleration can also be observed in DBA/2 mice (n = 33) and Line A mice (n = 15) using the BBA-seq approach.…”
Section: Genetic Background Impacts On Epigenetic Age-predictions Of mentioning
confidence: 68%
See 3 more Smart Citations
“…We have previously demonstrated, that epigenetic age-predictions with our 3 CpG pyrosequencing agepredictor are accelerated in DBA/2 mice, as compared to C57BL/6 mice, which may reflect the different life expectancy of these mouse strains (Han et al, 2018). Furthermore, we demonstrated that age-predictions with this predictor were also accelerated in C57BL/6 mice with quantitative trait locus insertion from DBA/2 into the congenic C57BL/6 chromosome 11, which was expected to be associated with the shorter lifespan of DBA/2 (referred to as Line A mice) (Brown et al, 2019). We now determined, within the same samples, whether the epigenetic age-acceleration can also be observed in DBA/2 mice (n = 33) and Line A mice (n = 15) using the BBA-seq approach.…”
Section: Genetic Background Impacts On Epigenetic Age-predictions Of mentioning
confidence: 68%
“…For epigenetic age predictions we either used (a) the 3 CpG multivariable model, or (b) the lasso regression model based on 7 CpGs of the same three amplicons (Prima1, Hsf4, Kcns1). As previously described for pyrosequencing, epigenetic age-predictions were logarithmically accelerated in DBA/2 mice (Han et al, 2018), and also accelerated in Line A mice (Brown et al, 2019).…”
Section: Genetic Background Impacts On Epigenetic Age-predictions Of mentioning
confidence: 95%
See 2 more Smart Citations
“…We have recently described an epigenetic clock that is based on pyrosequencing of DNAm at only three age-associated CpGs to facilitate a high accuracy with chronological age in C57BL/6 mice 17 . Notably, epigenetic aging was significantly accelerated in the shorter-lived DBA/2 mice 17 , and in congenic C57BL/6 mice harboring regions of chromosome 11 from DBA/2 mice likely linked to the regulation of lifespan (referred to as Line A mice) 18 . The epigenetic age was also decelerated by systemic administration of a drug that extended murine lifespan 19 , implying that the three CpGs might also serve as biomarkers of aging at least on an C57BL/6 background.…”
Section: Introductionmentioning
confidence: 99%